Business Competition Supervisory Institution: A Comparison between Indonesia and Thailand - Ayup Suran Ningsih (Jurnal Hukum Novelty, 2022)
Introduction to The Problem: Competition is necessary in the business world; business actors are no stranger to competition between business actors in their business activities. It is done solely for profit. Indonesia establishes the Business Competition Supervisory Commission (KPPU) as a form of the state's presence in protecting business actors who have been honest in carrying out their business activities.Purpose/Objective Study: This research aims to conduct comparative research related to the duties and powers of the business competition supervisory institution in Indonesia and Thailand to provide recommendations on issues related to strengthening the role of KPPU in Indonesia.Design/Methodology/Approach: This type of research is empirical legal research. The study employed the primary data through interview with KPPU and data from a literature review and analyzed it through the statue approach.Findings: Based on studying Thai Competition Act and The Thai Fair-Trade Commission (TFTC), the authors conclude that Indonesia Anti-Monopoly Act and Komisi Pengawas Persaingan Usaha (KPPU) are more simply and comprehensive in regulating business competition. Thailand has more than one institutions who handle the business competition, it is impressed more complicated and not integrated.Paper Type: Research Article